Influence of BaTiO3 NPs on Dielectric Characteristics of PVA/PEG For Electronic Applications. Issue 3 (May 2021) - Mohammed, Batool; Ahmed, Hind; Hashim, Ahmed
Abstract: In this paper, we synthesized new types of nanocomposites to be used in various electronic applications such as piezoelectric, pressure sensors, diodes, transistors with low cost and lightweight. The nanocomposites were obtained from PVA/PEG blend doped with nanoparticles BaTiO3 using casting method then studied using LCR meter. The dielectric characteristics of the synthesized nanocomposites have been studied. Results indicated that dielectric constants ε′, loss ε″ and conductivity σA.C in PVA/PEG rise as BaTiO3 NPs content increased. Also, the dielectric constant was increased from 5.8 to 8.6 and the dielectric loss was increased from 1.5 to 4.38. The ε′ and ε″ were decreased while the electrical conductivity was increased from 8.34 to 2.40 at 100 HZ and the σA.C was decreased with increasing frequency.